E-module innovation: a product-based approach to database practicum - Ermiyati Ermiyati; Nizwardi Jalinus; Waskito Waskito; Mukhlidi Muskhir (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Learning media is a crucial component in supporting the educational process. However, the practical learning process for the database subject at SMK Negeri 1 Sintuk Toboh Gadang has not fully prepared students to be independent and work-ready. This study aims to develop a product-based practicum module for the database subject, which is expected to enhance students' creativity, independence, and learning outcomes. The research method used is Research and Development (R&D) with the 4D model (define, design, develop, disseminate). Validation was conducted by media and content experts, followed by field trials involving 23 students. The research results show that the developed product-based e-module is valid with an average score of 0.85. The practicality of the module was rated very high, with a Reproducibility Coefficient of 0.98 and a Scalability Coefficient of 0.95. Its effectiveness was demonstrated through an improvement in student learning outcomes, with an N-Gain score of 0.73, categorized as high. Based on these findings, the module is considered valid, practical, and effective in improving student learning outcomes while promoting creativity and independence in database learning.